1999
DOI: 10.1136/bjsm.33.2.100
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of exercise-induced asthma in children by short, repeated warm ups.

Abstract: Aim-To study the eVect of a warm up schedule on exercise-induced asthma in asthmatic children to enable them to engage in asthmogenic activities. Method-In the first study, peak flows during and after three short, repeated warm up schedules (SRWU 1, 2, and 3), identical in form but diVering in intensity, were compared in 16 asthmatic children. In the second study the eYciency of the best of these SRWU schedules was tested on 30 young asthmatic children. Children performed on diVerent days a 7 minute run alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 18 publications
(11 reference statements)
2
19
0
3
Order By: Relevance
“…This is despite evidence that proper therapeutic management of asthma should allow most children to participate fully in vigorous physical activity, 36 particularly if a thorough warm-up is allowed. 37 If parents discourage exercise in children with asthma, the consequences may be secondary deconditioning as a result of inactivity. 38 This study provides some support for previous work, suggesting that asthma negatively impacts on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…This is despite evidence that proper therapeutic management of asthma should allow most children to participate fully in vigorous physical activity, 36 particularly if a thorough warm-up is allowed. 37 If parents discourage exercise in children with asthma, the consequences may be secondary deconditioning as a result of inactivity. 38 This study provides some support for previous work, suggesting that asthma negatively impacts on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Although physical training increases the aerobic capacity similarly in asthmatic patients and in healthy subjects, it has no detectable influence on the degree of EIA [39]. Conversely, a prolonged warm-up period of submaximal exercise can induce refractoriness of EIA without inducing bronchoconstriction [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…However, whole-body warm-up as well as hyperpnea warm-up exercises bear the risk of inducing EIB by itself [6,7,9,11,14] which might compromise preparation for the subsequent competition. Interestingly, one study showed that exercising with warm and humid air did not induce substantial EIB but this exercise was still effective in preventing EIB in the following exercise challenge [17].…”
Section: Introductionmentioning
confidence: 99%